ผลของโปรแกรมการฝึกพูดกับตัวเองทางบวกต่ออาการซึมเศร้าในผู้ป่วย โรคซึมเศร้าที่กลับมารักษาซ้ำ - ณัฏฐวิตรา ฤกษ์รัตนประทีป (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Major depressive disorder (MDD) usually involves a focus on negative situations and one's own failures. This can cause people to perceive themselves, the world and the future in a negative way. More than 50% of MDD patients are readmitted to the hospital for treatment. Positive self-talk is one form of psychosocial therapy that can help to reduce the symptoms of depression in patients who are readmitted. The purpose of this two-group pre- test and post-test quasi-experimental research study was to examine the effect of a positive self-talk training program on symptoms of depression in people who have been readmitted for major depressive disorder. The purposively selected participants included 52 people with mild to moderate levels of depression, 26 in the control group and 26 in the experimental group. The experimental group received routine care in addition to the positive self-talk training program, while the control group received routine care only. Research instruments consisted of: 1) demographic data form, 2) 9-Item Thai Patient Health Questionnaire (Thai PHQ-9), 3) The Positive Self-talk Training Program that was modified from a Positive Self-talk Training Program by Boonmeun (2016) based on the concept of Nelson-Jones (1990). Data were analyzed using descriptive statistics, paired t-test and independent t-test. The results of the study revealed that: 1. Mean scores for symptoms of depression in the experimental group were significantly lower at the post-test than at the pre-test p<.05 2. Mean scores for symptoms of depression were significantly lower in the experimental group than in the control group p< 0.5 at the post test. The results of this study indicated that a positive self-talk training program can help to reduce symptoms of depression among patients readmitted with major depressive disorder. Therefore, it can used to care for readmitted MDD patients who are experiencing symptoms of depression in Suan Prung Psychiatric Hospital.